Vinylpyridine-butadiene block copolymer, preparation method and application thereof, composition and application thereof, and polymer coating

By developing a vinylpyridine-butadiene block copolymer, the combination of anionic solution polymerization and specific structural regulators is used to solve the problems of high thermal expansion coefficient and poor adhesion to metal of liquid butadiene polymer, and the excellent thermal expansion performance and high adhesion of polymer coatings are achieved, and it is suitable for 5G high-frequency communication materials.

CN119912653APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311428421.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The thermal expansion coefficient of existing liquid butadiene polymers is relatively high, and their adhesion and adhesion to metals are not ideal, which cannot meet the demand for material performance of 5G high-frequency communication.

Method used

A vinylpyridine-butadiene block copolymer was developed to control the vinylpyridine segment content in 2-10% by weight and the butadiene segment content in 90-98% by weight through anionic solution polymerization. The structure of the polymer is optimized and its adhesion and thermal expansion properties with metals are improved.

Benefits of technology

The thermal expansion performance of the polymer coating and the adhesion of the metal substrate are significantly improved, and the formed coating has high peel strength and interlayer bonding force, which is suitable for the field of 5G high-frequency communications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004523031040000031
    Figure BDA0004523031040000031
  • Figure BDA0004523031040000101
    Figure BDA0004523031040000101
  • Figure BDA0004523031040000102
    Figure BDA0004523031040000102
Patent Text Reader

Abstract

The invention relates to the field of polymers, and discloses a vinylpyridine-butadiene block copolymer, a preparation method and application thereof, a composition and application thereof, and a polymer coating. On the basis of the total weight of the vinylpyridine-butadiene block copolymer, the content of the vinylpyridine chain segment is 2-10 wt%, and the content of the butadiene chain segment is 90-98 wt%; on the basis of the total weight of the butadiene chain segment, the content of the 1, 4-structural unit is 10-25 wt%, the content of the 1, 2-structural unit is 50-70 wt%, and the content of the cyclized 1, 2-structural unit is 15-35 wt%. A coating formed by the vinylpyridine-butadiene block copolymer shows improved thermal expansion performance, and meanwhile, the adhesive force and the bonding property of a liquid butadiene polymer and metal are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymers, and in particular to a vinylpyridine-butadiene block copolymer and a preparation method and application thereof, a composition of the vinylpyridine-butadiene block copolymer and an application thereof, and a polymer coating. Background Art

[0002] High vinyl narrow distribution liquid polybutadiene rubber has low dielectric constant and dielectric loss, low water absorption, high thermal cross-linking and photo-cross-linking activity, and excellent mechanical properties and heat resistance after cross-linking and curing. It is the most ideal cross-linking and curing material for 5G communication high-frequency copper clad laminates. Compared with conventional high vinyl liquid polybutadiene rubber, it has higher cross-linking activity and better heat resistance after cross-linking, but because liquid polybutadiene rubber only contains carbon and hydrogen elements, it has poor affinity with metal substrates.

[0003] CN113698520A discloses a liquid butadiene polymer with a number average molecular weight of 2500-5500, a molecular weight distribution of 1-1.2, and a vinyl content of 85-95%, and the liquid butadiene polymer has a lower dielectric constant, dielectric loss and film-forming properties, but the heat resistance and adhesion to metal are not satisfactory. CN114106228A discloses a method for preparing a liquid butadiene polymer and its products, which can meet the cross-linking and curing activity requirements of the high-end electronics industry, but also cannot solve the problems of heat resistance and adhesion and adhesion to metal. Therefore, it is of great significance to introduce polar groups into the molecular chain of high vinyl liquid polybutadiene rubber, improve adhesion to metal substrates, and meet the performance requirements of 5G high-frequency communications for key raw materials. Summary of the invention

[0004] In view of the technical problems that the liquid butadiene polymer prepared by the prior art has a relatively high thermal expansion coefficient and unsatisfactory adhesion and bonding to metals, the inventors of the present invention have conducted in-depth research on the anionic polymerization process of liquid butadiene polymers and developed a vinyl pyridine-butadiene block copolymer. The coating formed by the vinyl pyridine-butadiene block copolymer shows improved thermal expansion performance, while improving the adhesion and bonding to metals of the liquid butadiene polymer, thereby completing the present invention.

[0005] The first aspect of the present invention provides a vinylpyridine-butadiene block copolymer, characterized in that, based on the total weight of the vinylpyridine-butadiene block copolymer, the content of the vinylpyridine segment is 2-10% by weight, and the content of the butadiene segment is 90-98% by weight; based on the total weight of the butadiene segment, the content of the 1,4-structural unit is 10-25% by weight, the content of the 1,2-structural unit is 50-70% by weight, and the content of the cyclized 1,2-structural unit is 15-35% by weight.

[0006] The second aspect of the present invention provides a method for preparing a vinylpyridine-butadiene block copolymer, characterized in that the method comprises:

[0007] (1) in the presence of a solvent, a structure regulator and an initiator, continuously adding 1,3-butadiene monomer into a reactor to carry out anionic solution polymerization reaction to obtain a polymerization reaction solution containing a butadiene polymer, wherein the contact is carried out at a temperature of 60-100° C., the structure regulator comprises component A and component B, the component A is a tertiary amine, the component B is an alkali metal alcohol salt, the molar ratio of the component B to the component A is 0.1-0.5:1, and the solvent is a solvent containing an aliphatic heterocyclic ring;

[0008] (2) After the product obtained in step (1) is brought into contact with an alkyl metal compound for a first time, vinyl pyridine monomer is added for copolymerization to obtain a vinyl pyridine-butadiene block copolymer; wherein the amount of vinyl pyridine monomer added is 2-10 wt % based on the total weight of the 1,3-butadiene monomer and the vinyl pyridine monomer.

[0009] The third aspect of the present invention provides a vinylpyridine-butadiene block copolymer prepared by the above preparation method.

[0010] The fourth aspect of the present invention provides a composition comprising the above-mentioned vinylpyridine-butadiene block copolymer and at least one additive.

[0011] A fifth aspect of the present invention provides a polymer coating, which contains the above-mentioned vinylpyridine-butadiene block copolymer or the above-mentioned composition.

[0012] A sixth aspect of the present invention provides a use of the above-mentioned vinylpyridine-butadiene block copolymer or the above-mentioned composition as a cross-linking agent, an adhesive or an electrical insulating material.

[0013] Through the above technical scheme, the vinylpyridine-butadiene block copolymer provided by the present invention has good performance. The coating formed by the polymer not only has high peel strength and improved thermal expansion performance for the metal substrate, but also has strong bonding force between the coatings, and has broad application prospects in the field of communication technology. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] In the present invention, the term "liquid butadiene polymer" refers to a butadiene polymer having fluidity at 25°C and 1 standard atmospheric pressure.

[0016] In the present invention, the term "1,2-structural unit" refers to a structural unit formed by 1,3-butadiene in a 1,2-polymerization manner, and the content of 1,2-structural units may also be referred to as vinyl content. In the present invention, the content of 1,2-structural units in the polymer is determined by nuclear magnetic resonance spectroscopy.

[0017] In the present invention, the term "cyclized 1,2-structural unit" refers to the vinyl groups in two adjacent 1,2-structural units bonded to form a five-membered ring, and the specific structure is shown below:

[0018]

[0019] In the present invention, the content of cyclized 1,2-structural units in the polymer is determined by nuclear magnetic resonance spectroscopy.

[0020] In the present invention, the content of vinylpyridine structural units in the polymer is determined by nuclear magnetic resonance spectroscopy.

[0021] In the present invention, the specific test method of nuclear magnetic resonance spectroscopy is: using a Bruker AVANCE400 superconducting nuclear magnetic resonance wave instrument ( 1 H-NMR) test, 1 The resonance frequency of the H nucleus is 400.13 MHz, the spectral width is 2747.253 Hz, the pulse width is 5.0 μs, the data point is 16 K, the sample tube diameter is 5 mm, the solvent is deuterated chloroform (CDCl3), the sample concentration is 15% (mg / mL), the test temperature is room temperature (25°C), the number of scans is 16 times, and the chemical shift of tetramethylsilane is calibrated to 0 ppm.

[0022] In the present invention, molecular weight and molecular weight distribution index (M w / M n ) was determined by gel permeation chromatography. The specific test method was: using HLC-8320 gel permeation chromatograph produced by Tosoh Corporation of Japan, the chromatographic column was TSKgelSuperMultiporeHZ-N, the standard column was TSKgel SuperMultiporeHZ, the solvent was chromatographic pure tetrahydrofuran (THF), and narrow distribution polystyrene was used as the standard sample. The polymer sample was prepared into a tetrahydrofuran solution with a concentration of 1 mg / mL, the injection volume was 10 μL, the flow rate was 0.35 mL / min, and the test temperature was 40°C.

[0023] In the present invention, the content of metal elements in the polymer is determined by plasma method, and the specific test method is: using the Optima 8300 full-spectrum direct-reading ICP spectrometer of PerkinElmer (PE) of the United States, equipped with a medium-step grating, a solid-state detector, a dual-path dual solid-state detector in the ultraviolet light region and the visible light region, and using flat-panel plasma technology; the instrument operating parameters are as follows: high-frequency power 1300W, plasma gas flow 15L / min, atomizing gas flow 0.55L / min, auxiliary gas flow 0.2L / min, peristaltic pump speed 1.50mL / min, integration time 10s, plasma axial observation. The sample preparation method is as follows: accurately weigh 2.000g of the sample in a porcelain crucible, place it in a high-temperature resistance furnace and gradually heat it to 500℃, take it out after complete ashing, add 5mL of 10 volume % dilute nitric acid, slowly heat it on a hot plate until it is completely dissolved, evaporate the solution to dryness, add 1mL of concentrated nitric acid, transfer it to a 50mL volumetric flask, and make up to volume with water, and prepare a reagent blank solution at the same time.

[0024] In the present invention, the linear thermal expansion coefficient is measured by thermomechanical analysis (TMA) according to the method specified in GB / T 36800.2-2018.

[0025] In the present invention, the peel strength between the polymer coating and the metal substrate (copper foil) is tested using the method specified in IPC-TM-650.

[0026] In the present invention, the interlayer bonding strength of the metal substrate after the polymer coating is cured is tested according to the DB44T1088-2012 standard.

[0027] The first aspect of the present invention provides a vinylpyridine-butadiene block copolymer, characterized in that, based on the total weight of the vinylpyridine-butadiene block copolymer, the content of the vinylpyridine segment is 2-10% by weight, and the content of the butadiene segment is 90-98% by weight; based on the total weight of the butadiene segment, the content of the 1,4-structural unit is 10-25% by weight, the content of the 1,2-structural unit is 50-70% by weight, and the content of the cyclized 1,2-structural unit is 15-35% by weight.

[0028] According to the present invention, based on the total weight of the vinylpyridine-butadiene block copolymer, the content of the vinylpyridine segment is 2-10% by weight. In the present invention, the inventors have found that when the content of the vinylpyridine segment in the copolymer is controlled to meet the above range, the adhesion of the coating formed by the polymer to the metal substrate can be significantly improved, and the dielectric loss of the polymer coating can be reduced. Specifically, when the content of the acrylate segment is less than 2% by weight, the adhesion of the coating formed by the polymer to the metal is not significantly improved; when the content of the vinylpyridine segment is greater than 10% by weight, the dielectric loss of the polymer coating increases. Based on the total weight of the vinylpyridine-butadiene block copolymer, the content of the acrylate segment can be 2% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, preferably 4-8% by weight.

[0029] In the present invention, in the vinylpyridine-butadiene block copolymer, the butadiene segment is a high-vinyl cyclized butadiene segment.

[0030] According to the present invention, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of 1,4-structural units is 10-25% by weight, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25% by weight. Preferably, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of 1,4-structural units is 10-20% by weight. When the content of 1,4-structural units is less than 10% by weight, it is necessary to carry out at a lower temperature, which affects the content of cyclized structural units of the polymer; when the content of 1,4-structural units is greater than 25% by weight, the double bonds that can participate in curing and crosslinking are reduced, the crosslinking density of the polymer coating is reduced, and the mechanical properties are deteriorated.

[0031] According to the present invention, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of 1,2-structural units is 50-70% by weight, for example, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69 or 70% by weight. Preferably, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of 1,2-structural units is 50-65% by weight. More preferably, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of 1,2-structural units is 52-62% by weight. When the content of 1,2-structural units is less than 50% by weight, the crosslinking density of the coating formed by the polymer decreases and the mechanical properties deteriorate; when the content of 1,2-structural units is greater than 70% by weight, the content of cyclized 1,2-structural units decreases, which is not conducive to improving the thermal expansion coefficient.

[0032] According to the present invention, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of the cyclized 1,2-structural unit is 15-35% by weight, such as 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 or 35% by weight. Preferably, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of the cyclized 1,2-structural unit is 18-35% by weight. More preferably, based on the total weight of the butadiene segments in the vinylpyridine-butadiene block copolymer, the content of the cyclized 1,2-structural unit is 20-35% by weight. In the present invention, if the content of cyclized 1,2-structural units is less than 15% by weight, the thermal expansion coefficient of the coating after curing is not significantly improved; if the content of cyclized 1,2-structural units is greater than 35% by weight, in order to prepare liquid polybutadiene rubber with a higher cyclized structure content, increasing the polymerization temperature becomes the only option, which is not conducive to increasing the total 1,2-structure content of the polymer, and the peel strength between the coating formed by the polymer and the metal substrate decreases, and the interlayer bonding force between copper foils decreases after the polymer coating is cured.

[0033] According to the present invention, the molar ratio of the cyclized 1,2-structural unit to the 1,2-structural unit in the vinylpyridine-butadiene block copolymer is 0.2-0.7:1.

[0034] In the present invention, when the molar ratio of the cyclized 1,2-structural unit to the 1,2-structural unit in the vinylpyridine-butadiene block copolymer meets the above range, the comprehensive performance of the polymer coating after curing is better.

[0035] Furthermore, the molar ratio of the cyclized 1,2-structural unit to the 1,2-structural unit in the vinylpyridine-butadiene block copolymer is 0.3-0.6:1.

[0036] According to the present invention, the number average molecular weight (M) of the vinyl pyridine-butadiene block copolymer is n ) is 3000-10000 g / mol, preferably 5000-8500 g / mol.

[0037] According to the present invention, the vinyl pyridine-butadiene block copolymer not only has a molecular weight suitable for molding, but also has a narrow molecular weight distribution. Generally, according to the present invention, the molecular weight distribution index (M w / M n ) is 1-1.25, preferably 1-1.15.

[0038] According to the present invention, based on the total weight of the vinylpyridine-butadiene block copolymer, the weight content of the metal element in the polymer is 200 ppm or less, preferably 100 ppm or less, more preferably 50 ppm or less, and further preferably 20 ppm or less. Controlling the metal content in the polymer is conducive to reducing the dielectric constant and dielectric loss of the cross-linked and cured product, thereby obtaining better applications in the field of electronic communications.

[0039] According to the present invention, the linear thermal expansion coefficient of the vinyl pyridine-butadiene block copolymer after curing is 45×10 -6 m / m / ℃-80×10 -6 m / m / ℃, preferably 50×10 -6 m / m / ℃-75×10 -6 m / m / ℃, more preferably 50×10 - 6 m / m / ℃-70×10 -6 m / m / ℃.

[0040] According to the present invention, the peel strength between the coating formed by the vinylpyridine-butadiene block copolymer and the metal substrate (such as copper foil) is 0.9-1.2 N / mm, preferably 1.02-1.2 N / mm, and more preferably 1.05-1.2 N / mm.

[0041] According to the present invention, after the coating formed by the vinylpyridine-butadiene block copolymer is cured, the interlayer bonding force of the metal substrate is 0.8-1.1 N / mm, preferably 0.86-1.1 N / mm, and more preferably 0.95-1.1 N / mm.

[0042] A second aspect of the present invention provides a method for preparing a vinylpyridine-butadiene block copolymer, the method comprising:

[0043] (1) in the presence of a solvent, a structure regulator and an initiator, continuously adding 1,3-butadiene monomer into a reactor to carry out anionic solution polymerization reaction to obtain a polymerization reaction solution containing a butadiene polymer, wherein the contact is carried out at a temperature of 60-100° C., the structure regulator comprises component A and component B, the component A is a tertiary amine, the component B is an alkali metal alcohol salt, the molar ratio of the component B to the component A is 0.1-0.5:1, and the solvent is a solvent containing an aliphatic heterocyclic ring;

[0044] (2) After the product obtained in step (1) is brought into contact with an alkyl metal compound for a first time, vinyl pyridine monomer is added for copolymerization to obtain a vinyl pyridine-butadiene block copolymer; wherein the amount of vinyl pyridine monomer added is 2-10 wt % based on the total weight of the 1,3-butadiene monomer and the vinyl pyridine monomer.

[0045] In the present invention, the term “continuously” means that the 1,3-butadiene monomer required for polymerization is added gradually and continuously into the reactor, rather than adding all the 1,3-butadiene monomer required for polymerization into the reactor at one time.

[0046] In the present invention, by continuously adding the 1,3-butadiene monomer required for polymerization into the reactor, the polymerization reaction can be precisely controlled, ensuring that the active species of the initiator are always in a hungry state, which is more conducive to the formation of the 1,2-cyclized structure. Further, the content of the cyclized 1,2-structure in the butadiene polymer is increased, and the butadiene polymer with a high content of cyclized 1,2-structure is contacted with an alkyl metal compound and then copolymerized with a vinyl pyridine monomer to obtain the acrylate-butadiene block polymer described in the first aspect of the present invention. In particular, when the amount of the vinyl pyridine monomer added in the 1,3-butadiene monomer and the vinyl pyridine monomer meets the above range, the adhesion between the polymer and the metal substrate can be significantly improved, and the thermal expansion coefficient and dielectric loss of the polymer coating after curing can also be controlled within an ideal range.

[0047] In the present invention, in the vinylpyridine-butadiene block copolymer, the 1,2-structural unit content, the 1,4-structural unit content and the cyclized 1,2-structural unit content in the butadiene segment are determined by step (1), and the copolymerization reaction with the vinylpyridine monomer in step (2) does not affect the 1,2-structural unit content, the 1,4-structural unit content and the cyclized 1,2-structural unit content in the butadiene segment.

[0048] Furthermore, based on the total weight of the 1,3-butadiene monomer and the vinyl pyridine monomer, the amount of the vinyl pyridine monomer added is 4-8% by weight.

[0049] According to the present invention, the conditions of the copolymerization reaction include: a polymerization temperature of 20° C. to 60° C., and a polymerization time of 10-30 min.

[0050] Furthermore, the conditions of the copolymerization reaction include: a polymerization temperature of 30° C. to 50° C., and a polymerization time of 20-30 min.

[0051] According to the present invention, the vinyl pyridine monomer is selected from 2-vinyl pyridine and / or 4-vinyl pyridine.

[0052] According to the present invention, based on 100 g of solvent, the rate of adding 1,3-butadiene into the reactor is 0.1-0.5 g / min, preferably 0.15-0.35 g / min.

[0053] According to the present invention, butadiene monomer is continuously processed at a temperature of 60°C to 90°C, preferably at a temperature of 70°C to 90°C.

[0054] In the present invention, the anionic solution polymerization reaction can be carried out under a pressure of 0.005-1.5MPa, more preferably under a pressure of 0.1-1MPa, and further preferably under a pressure of 0.2-0.6MPa. In the present invention, pressure refers to gauge pressure. The polymerization time can be selected according to the final monomer concentration and polymerization temperature of the polymerization reaction, and can generally be 30-120min, preferably 40-80min.

[0055] In the present invention, the anionic polymerization reaction is carried out in an atmosphere formed by an inert gas. The inert gas refers to a gas that does not chemically interact with reactants, reaction products and solvents under polymerization conditions, such as nitrogen and / or zero group element gas (such as argon).

[0056] According to the present invention, in step (2), the alkyl metal compound is selected from alkyl aluminum compounds and / or alkyl magnesium compounds.

[0057] According to the present invention, the alkyl metal compound is at least one selected from trimethylaluminum, triethylaluminum, tripropylaluminum, triisopropylaluminum, tributylaluminum, triisobutylaluminum, diethylmagnesium, dibutylaluminum and n-butyl-sec-butylmagnesium.

[0058] According to the present invention, the molar ratio of the alkyl metal compound to the initiator is 1-5:1.

[0059] In the present invention, when the molar ratio of the alkyl metal compound to the initiator is controlled to meet the above range, the side reaction in the anionic polymerization process of vinyl pyridine can be suppressed to prepare a butadiene-vinyl pyridine block polymer.

[0060] Furthermore, the molar ratio of the alkyl metal compound to the initiator is 1-2:1.

[0061] According to the present invention, the time for the first contact between the product obtained in step (1) and the alkyl metal compound is 1-10 minutes.

[0062] In the present invention, the product containing the active chain of butadiene polymer obtained in step (1) is first contacted with an alkyl metal compound in advance, and the time of the first contact is specifically controlled to meet the above range, so that the butadiene active chain and the metal alkyl compound form a complex with a specific structure, the anionic polymerization activity of vinyl pyridine is reduced, and a butadiene-vinyl pyridine block polymer is prepared.

[0063] Furthermore, the first contact time between the product obtained in step (1) and the alkyl metal compound is 2-8 minutes.

[0064] In a preferred embodiment, the component A is one or more compounds selected from the group consisting of compounds shown in formula I.

[0065]

[0066] In formula I, R2 and R3 are the same or different and are each independently a C1-C6 alkyl group.

[0067] In formula I, R1 is a monovalent group shown in formula II,

[0068]

[0069] In Formula II, m is an integer of 1-5, for example, 1, 2, 3, 4 or 5.

[0070] In formula II, R4 and R5 are the same or different and are independently a hydrogen atom or a C1-C6 alkyl group, preferably a hydrogen atom.

[0071] In formula II, R6 is -NR7R8, or a C3-C6 oxacycloalkyl group, and R7 and R8 are the same or different and are each independently a C1-C6 alkyl group.

[0072] In Formula I and Formula II, the C1-C6 alkyl group includes a C1-C6 straight-chain alkyl group and a C3-C6 branched-chain alkyl group, and specific examples thereof may include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl and n-hexyl.

[0073] In a preferred embodiment of the present invention, the component A is N,N,N',N'-tetramethylethylenediamine and / or N,N-dimethyltetrahydrofurfurylamine. In a particularly preferred embodiment, the component A is N,N,N',N'-tetramethylethylenediamine.

[0074] In a preferred embodiment, the component B is one or more compounds selected from the group consisting of compounds shown in formula III.

[0075] R9-O-M1 (Formula III)

[0076] In formula III, R9 is C1-C 20 Alkyl, C1-C 20 Alkyl or C6-C 30 The aromatic group,

[0077] M1 is an alkali metal atom, such as Li, Na or K, preferably Na.

[0078] In Formula III, C1-C 20 The alkyl groups include C1-C 20 Straight chain alkyl and C3-C 20Specific examples of the branched alkyl group may include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl and its isomers, n-hexyl and its isomers, n-heptyl and its isomers, n-octyl and its isomers, n-nonyl and its isomers, n-decyl and its isomers, undecyl and its isomers, dodecyl and its isomers, tridecyl and its isomers, tetradecyl and its isomers, pentadecyl and its isomers, hexadecyl and its isomers, heptadecyl and its isomers, octadecyl and its isomers, nonadecyl and its isomers, and eicosyl and its isomers.

[0079] In Formula III, the C1-C 20 The substituent in the alkyl group is preferably a cycloalkyl group containing a heteroatom, and specific examples of the heteroatom may include, but are not limited to, an oxygen atom, a sulfur atom or a nitrogen atom. In a preferred embodiment, the heteroatom in the substituent containing a heteroatom is an oxygen atom, and the substituent containing a heteroatom is a cycloalkyl group containing an oxygen atom, such as an acrylate substituent, an oxetane substituent, an oxetane substituent, a tetrahydrofuran substituent, or an oxetane substituent.

[0080] In Formula III, C6-C 30 Specific examples of the aryl group may include, but are not limited to, phenyl, o-tolyl, m-tolyl, p-tolyl, o-ethylphenyl, m-ethylphenyl, p-ethylphenyl, o-tert-butylphenyl, m-tert-butylphenyl, p-tert-butylphenyl, p-dodecylphenyl, 2,4-di-n-butylphenyl, p-n-propylphenyl, and 2,4-diethylphenyl.

[0081] In a preferred embodiment of the present invention, the component B is preferably one or more of sodium tetrahydrofurfuryl alcohol, sodium tert-amyl oxide, sodium tert-butoxylate, sodium n-hexoxide and sodium menthol.

[0082] In a preferred embodiment of the present invention, the molar ratio of component B to component A is 0.1-0.5:1, preferably 0.15-0.45:1, and more preferably 0.2-0.4:1.

[0083] In a preferred embodiment of the present invention, the amount of the structure regulator can be adjusted according to the amount of the monomer (i.e., 1,3-butadiene) and / or the anionic polymerization initiator. Relative to 1 mol of the initiator, the amount of the component A can be 0.5-2 mol, preferably 0.7-1.5 mol. Relative to 1 mol of the initiator, the amount of the component B can be 0.1-0.5 mol, preferably 0.2-0.4 mol.

[0084] In a preferred embodiment of the present invention, the initiator is an organic lithium initiator, preferably an organic monolithium compound, and more preferably a compound represented by formula IV.

[0085] R 10 Li (Formula IV)

[0086] In Formula IV, R 10 C1-C6 alkyl, C3-C 12 Cycloalkyl, C7-C 14 Arylalkyl or C6-C 12 The aromatic group.

[0087] In formula IV, the C1-C6 alkyl group includes C1-C6 straight-chain alkyl groups and C3-C6 branched-chain alkyl groups, and specific examples thereof may include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl and n-hexyl.

[0088] In Formula IV, C3-C 12 Specific examples of the cycloalkyl group may include, but are not limited to, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, 4-ethylcyclohexyl, 4-n-propylcyclohexyl, and 4-n-butylcyclohexyl.

[0089] In Formula IV, C7-C 14 Specific examples of the aralkyl group may include, but are not limited to, phenylmethyl, phenylethyl, phenyl-n-propyl, phenyl-n-butyl, phenyl-t-butyl, phenyl-isopropyl, phenyl-n-pentyl, and phenyl-n-butyl.

[0090] In Formula IV, C6-C 12 Specific examples of the aryl group may include, but are not limited to, phenyl, naphthyl, 4-methylphenyl, and 4-ethylphenyl.

[0091] In a preferred embodiment of the present invention, specific examples of the initiator may include, but are not limited to: one or more of ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, phenyl lithium, 2-naphthyl lithium, 4-butylphenyl lithium, 4-tolyl lithium, cyclohexyl lithium and 4-butylcyclohexyl lithium. Preferably, the initiator is n-butyl lithium and / or sec-butyl lithium, and more preferably, the initiator is n-butyl lithium.

[0092] In the present invention, the amount of the anionic polymerization initiator can be selected according to the expected number average molecular weight of the vinyl pyridine-butadiene block polymer. Preferably, the amount of the anionic polymerization initiator is such that the number average molecular weight of the prepared liquid butadiene polymer is 3000-10000 g / mol, preferably 5000-8500 g / mol. The method for determining the specific amount of the anionic polymerization initiator according to the expected polymer molecular weight is well known to those skilled in the art and will not be described in detail herein.

[0093] According to the present invention, the solvent is a solvent containing an aliphatic heterocycle. The term "aliphatic heterocycle" refers to a cycloalkane in which at least one carbon atom on the ring is replaced by a heteroatom. The heteroatom in the aliphatic heterocycle can be an oxygen atom, a nitrogen atom or a sulfur atom, preferably an oxygen atom. The solvent can be one or more selected from tetrahydrofuran, cyclopentane oxide, cyclohexane oxide and 1,4-dioxane. The solvent can be used alone or in combination. In a preferred embodiment, the solvent is an aliphatic heterocycle solvent, more preferably an oxacycloalkane. In a particularly preferred embodiment, the solvent is tetrahydrofuran.

[0094] In the present invention, the content of 1,3-butadiene monomer can be 1-40% by weight, preferably 10-30% by weight, based on the total weight of the solvent and the 1,3-butadiene monomer. In the present invention, the content of 1,3-butadiene monomer refers to the total weight percentage of 1,3-butadiene monomer determined based on the total weight of the solvent and the 1,3-butadiene monomer after the polymerization reaction.

[0095] In the present invention, the preparation method further comprises: after the copolymerization reaction is completed, adding a terminator, removing the organic lithium initiator and the solvent, and obtaining the vinyl pyridine-butadiene block copolymer.

[0096] In the present invention, there is no particular limitation on the type and amount of the terminator, and conventional terminators in the art may be used and added in conventional amounts in the art.

[0097] In the present invention, the preparation method may further include: removing at least part of the metal ions in the polymerization reaction mixture to obtain a purified polymerization reaction mixture. The polymerization reaction mixture may be washed to remove at least part of the metal ions.

[0098] In a preferred embodiment, the method for removing at least part of the metal ions in the polymerization mixture comprises: mixing the polymerization mixture with a washing liquid, and separating the oil phase from the mixture, wherein the washing liquid is water or an aqueous solution containing an acid. In this preferred embodiment, the acid is preferably an inorganic acid, more preferably one or more of sulfuric acid, nitric acid, hydrochloric acid and carbonic acid. When the acid is carbonic acid, carbonic acid can be formed by passing carbon dioxide gas into the mixture of the polymerization mixture and water and / or adding dry ice to the polymerization mixture.

[0099] In a more preferred example of this preferred embodiment, the washing liquid includes a first washing liquid and a second washing liquid, the first washing liquid is an aqueous solution containing acid I, the second aqueous solution is an aqueous solution containing acid II, the acid I is one or more of sulfuric acid, hydrochloric acid and nitric acid, and the acid II is carbonic acid, and the method for removing at least part of the metal ions in the polymerization reaction mixture comprises: mixing the polymerization reaction mixture with the first washing liquid to obtain a first mixture, separating a first oil phase from the first mixture, removing at least part of the solvent in the first oil phase, and obtaining a crude product of liquid butadiene polymer; in the presence of carbon dioxide, mixing the first oil phase with water to obtain a second mixture, separating a second oil phase from the second mixture, removing at least part of the volatile components in the second oil phase, and obtaining a liquid butadiene polymer. In this more preferred example, the weight ratio of the first washing liquid to the monomer is preferably 1-5:1, more preferably 2-4:1, the molar ratio of the acid I in the first washing liquid to the anionic polymerization initiator is preferably 0.5-3:1, more preferably 0.8-2:1, and the acid I is in the form of H + The weight ratio of the second washing liquid to the monomer is 1-2: 1, the molar ratio of the acid II in the second washing liquid to the anionic polymerization initiator is preferably 0.1-1: 1, the acid II to H + count.

[0100] In the present invention, various reagents used in the preparation method are preferably refined by conventional methods in the art before use to remove impurities (especially water) therein. The method for refining the reagents is well known in the art and will not be described in detail herein.

[0101] In the present invention, the anionic solution polymerization reaction can be carried out by batch polymerization or continuous polymerization, without particular limitation.

[0102] The third aspect of the present invention provides a vinylpyridine-butadiene block copolymer prepared by the above method.

[0103] The butadiene segments in the vinylpyridine-butadiene block copolymer prepared by the method described in the second aspect of the present invention not only have a high 1,2-structural unit content, but also part of the 1,2-structural units form a cyclic structure, and contain vinylpyridine segments. The coating formed by the raw materials containing the vinylpyridine-butadiene block copolymer prepared by the method described in the second aspect of the present invention shows more excellent thermal expansion performance while maintaining high peel strength and interlayer bonding strength.

[0104] The fourth aspect of the present invention provides a composition, which comprises the above-mentioned vinylpyridine-butadiene block copolymer and at least one additive.

[0105] In the present invention, the additive can be a substance that can give the composition new properties and / or improve the existing properties of the composition. As a preferred example, the additive contains an antioxidant. The antioxidant can be a conventional selection, for example, the antioxidant can be a phenolic and / or amine antioxidant. Specifically, the antioxidant can be one or more of 4,6-dioctylthiomethyl o-cresol, tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester (i.e., antioxidant 264), tris(2,4-di-tert-butylphenyl) phosphite (i.e., antioxidant 168), 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid octadecyl ester (i.e., antioxidant 1076), 2,6-di-tert-butyl-p-cresol, tert-butylcatechol and 2,2'-methylene-bis(4-methyl-6-tert-butylphenol). The content of the antioxidant may be 0.005-2 parts by weight, preferably 0.01-1 parts by weight, relative to 100 parts by weight of the acrylate-butadiene block polymer.

[0106] The fifth aspect of the present invention provides a polymer coating, which contains the above-mentioned vinyl pyridine-butadiene block copolymer or the above-mentioned composition.

[0107] In the present invention, the polymer coating not only has high adhesion and bonding to the substrate, but also has a reduced thermal expansion coefficient, showing improved thermal expansion performance.

[0108] A sixth aspect of the present invention provides a use of the above-mentioned vinylpyridine-butadiene block copolymer or the above-mentioned composition as a cross-linking agent, an adhesive or an electrical insulating material.

[0109] The present invention will be described in detail below with reference to the embodiments, but the scope of the present invention is not limited thereby.

[0110] Unless otherwise specified, normal temperature and room temperature both refer to 25±3℃.

[0111] In the following examples and comparative examples, the microstructure of the polymer was measured using a Bruker AVANCE400 superconducting nuclear magnetic resonance instrument ( 1 H-NMR) determination, 1 The resonance frequency of the H nucleus is 400.13 MHz, the spectral width is 2747.253 Hz, the pulse width is 5.0 μs, the data point is 16 K, the sample tube diameter is 5 mm, the solvent is deuterated chloroform (CDCl3), the sample concentration is 15% (W / V), the test temperature is room temperature, the number of scans is 16 times, and the chemical shift is calibrated with tetramethylsilane as 0 ppm.

[0112] In the following examples and comparative examples, the molecular weight and molecular weight distribution index of the polymer were determined by gel permeation chromatography analysis. The gel permeation chromatography analysis was performed using an HLC-8320 gel permeation chromatograph produced by Tosoh Corporation of Japan. The chromatographic column was TSKgel SuperMultiporeHZ-N, the standard column was TSKgel SuperMultiporeHZ, the solvent was chromatographically pure tetrahydrofuran (THF), and narrow distribution polystyrene was used as the standard sample. The polymer sample was prepared into a tetrahydrofuran solution with a mass concentration of 1 mg / mL, the injection volume was 10.00 μL, the flow rate was 0.35 mL / min, and the test temperature was 40.0°C.

[0113] In the following examples and comparative examples, the linear thermal expansion coefficient is measured by thermomechanical analysis (TMA) according to the method specified in GB / T 36800.2-2018.

[0114] In the following examples and comparative examples, the peel strength between the polymer coating and the copper foil was tested using the method specified in IPC-TM-650 2.4.08C.

[0115] In the following examples and comparative examples, the interlayer bonding strength of the copper foil is tested according to the DB44T1088-2012 standard.

[0116] In the following examples and comparative examples, the following chemical reagents are involved:

[0117] Antioxidant 264, antioxidant 168 and antioxidant 1076 were purchased from Sinopharm Reagent Company.

[0118] Tetrahydrofuran: chromatographically pure, soaked on molecular weight sieves for 15 days, water content less than 5ppm (weight content).

[0119] 1,3-Butadiene: polymerization grade, purchased from Yanshan Petrochemical.

[0120] n-Butyl lithium: purchased from J&K Reagent Company, as a 1.6 mol / L hexane solution.

[0121] 2,2-Di(2-tetrahydrofuryl)propane (DTHFP): purchased from J&K Reagent Co., analytical grade.

[0122] N,N,N',N'-Tetramethylethylenediamine (TMEDA): purchased from J&K Reagent Co., analytical grade.

[0123] Sodium tert-amyloxide (STA): purchased from J&K Reagent Company, 1.4 mol / L tetrahydrofuran solution.

[0124] Sodium tetrahydrofurfuryl alcohol (THFOA): purchased from Inotech Reagent Company, 1.0 mol / L tetrahydrofuran solution.

[0125] Sodium menthol (SMT): purchased from Inotech Reagent Company, 1.0 mol / L tetrahydrofuran solution.

[0126] Vinylpyridine (VP): purchased from Inotech Reagent Company, purity 97%.

[0127] Triisobutylaluminum (Al): purchased from Inotech Reagent Company, 1.0 mol / L hexane solution.

[0128] n-Butylmagnesium (Mg): purchased from Inotech Reagent Company, 1.0 mol / L hexane solution.

[0129] Sulfuric acid: purchased from J&K Reagent Company, concentration is 98 wt%, prepared with water to make a 20 wt% solution.

[0130] Nitric acid: purchased from Sinopharm Reagent Company, with a concentration of 68% by weight, prepared with water to a 20% by weight solution.

[0131] Example 1

[0132] This example is used to illustrate the vinyl pyridine-butadiene block copolymer and its preparation method of the present invention.

[0133] (1) Under nitrogen protection, tetrahydrofuran (THF), structure regulator 1, structure regulator 2, and n-butyl lithium (types and amounts are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds) are added to a 5 L reactor, the temperature in the reactor is controlled to be the polymerization reaction temperature listed in Table 1, and 1,3-butadiene monomer is continuously added to the reactor (the addition rate and time are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds); and anionic solution polymerization is carried out at the temperature and pressure listed in Table 1 to obtain a polymerization reaction mixture containing a high vinyl cyclized liquid butadiene polymer.

[0134] (2) Adding a designed amount of an alkyl aluminum (magnesium) compound (the type and amount are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds) to the high-vinyl cyclized liquid butadiene polymer reaction mixture obtained in step (1), adding a designed amount of vinyl pyridine (the type and amount are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds) after the reaction is completed, and conducting anionic solution polymerization at the temperature and pressure listed in Table 1 to obtain a reaction solution containing a vinyl pyridine-butadiene block copolymer.

[0135] (3) Add water and acid (specific amounts and types of acid are listed in Table 2, and the amounts listed in Table 2 are all measured based on pure compounds) to the reaction solution obtained in step (2), stir for 15 minutes, and then stand for stratification to separate the aqueous phase. The obtained oil phase is distilled under reduced pressure to obtain a crude product containing vinyl pyridine-butadiene block copolymer.

[0136] (4) adding water to the crude product containing vinyl pyridine-butadiene block copolymer obtained in step (3), introducing carbon dioxide gas with stirring (the specific amounts of water and carbon dioxide are listed in Table 2), then standing to separate the layers, separating the aqueous phase, subjecting the obtained oil phase to reduced pressure distillation, and adding an antioxidant to the distillation residue (the specific amount and type are listed in Table 2) to obtain a composition LPB1 containing vinyl pyridine-butadiene block copolymer, wherein the structural property parameters of the vinyl pyridine-butadiene block copolymer are listed in Table 3.

[0137] Embodiment 2-10

[0138] Examples 2-10 are used to illustrate the vinyl pyridine-butadiene block copolymer and the preparation method thereof of the present invention.

[0139] Example 2-10 uses the same method as Example 1 to prepare a composition containing vinyl pyridine-butadiene block copolymer, except that step (1) and step (2) are reacted under the conditions shown in Table 1, and step (3) and step (4) are used to treat the reaction mixture containing vinyl pyridine-butadiene block copolymer obtained in step (1) under the conditions shown in Table 2, thereby respectively obtaining compositions LPB2-LPB10 containing vinyl pyridine-butadiene block copolymer, wherein the structural property parameters of the vinyl pyridine-butadiene block copolymer are listed in Table 3.

[0140] Comparative Example 1

[0141] A vinyl pyridine-butadiene block copolymer was prepared by the same method as in Example 1, except that no alkyl aluminum was added in step (2). A composition DLPB1 containing a vinyl pyridine-butadiene block copolymer was obtained. The structural property parameters of the vinyl pyridine-butadiene block copolymer are listed in Table 3.

[0142] Comparative Example 2

[0143] The liquid butadiene polymer was prepared in the same manner as in Example 1, except that alkyl aluminum and vinyl pyridine were not added, to obtain a composition DLPB2 containing a liquid butadiene polymer, wherein the structural property parameters of the liquid butadiene polymer are listed in Table 3.

[0144] Comparative Example 3

[0145] A composition containing vinyl pyridine-butadiene block copolymer was prepared by the same method as in Example 1, except that 5 g of vinyl pyridine was added in step (2) to obtain a composition DLPB3 containing vinyl pyridine-butadiene block copolymer. The structural property parameters of the vinyl pyridine-butadiene block copolymer are listed in Table 3.

[0146] Comparative Example 4

[0147] A composition containing vinyl pyridine-butadiene block copolymer was prepared by the same method as in Example 1, except that 80 g of vinyl pyridine was added to obtain a composition DLPB4 containing vinyl pyridine-butadiene block copolymer. The structural property parameters of the vinyl pyridine-butadiene block copolymer are listed in Table 3.

[0148] Table 1

[0149]

[0150]

[0151] a Based on 100g solvent

[0152] Table 1

[0153]

[0154] a Based on 100g solvent

[0155] Table 2

[0156]

[0157]

[0158] b Relative to 100g vinylpyridine-butadiene block copolymer

[0159] Table 3

[0160]

[0161] Note: VP represents vinylpyridine segment, PB represents butadiene segment, Mn represents the number average molecular weight of vinylpyridine-butadiene block copolymer, Mw / Mn represents the molecular weight distribution of vinylpyridine-butadiene block copolymer, 1,2-PB represents the content of 1,2-structure in butadiene segment, C-1,2-PB represents the content of cyclized 1,2-structure in butadiene segment, and 1,4-PB represents the content of 1,4-structural unit in butadiene segment.

[0162] It can be seen from Table 3 that the vinylpyridine-butadiene block copolymer provided by the present invention contains both butadiene segments and vinylpyridine segments, and the butadiene segments have a higher 1,2-structural unit content and a cyclized 1,2-structural unit content, and a narrow molecular weight distribution, and is an ideal rubber for the high-frequency communication field.

[0163] Test Case

[0164] Compositions LPB1 to LPB10 (wherein the vinyl pyridine-butadiene block copolymer is 100 g and the antioxidant is 0.16 g) prepared in Examples 1-10 were evenly coated on the surface of the copper foil with a coating thickness of 0.8 mm. The coating was cross-linked and cured at 120° C. for 2 hours. The peel strength was determined by the method specified in IPC-TM-650 2.4.08C. The interlayer bonding force between the copper foils was tested according to the method specified in DB44T1088-2012. The linear thermal expansion coefficient of the polymer coating was determined by thermomechanical analysis (TMA) according to the method specified in GB / T 36800.2-2018. The experimental results are listed in Table 4.

[0165] Test comparison

[0166] The peel strength and thermal expansion coefficient of the compositions DLPB1 to DLPB4 prepared in Comparative Examples 1-4 were measured using the same method as in the test example. The experimental results are listed in Table 4.

[0167] Table 4

[0168]

[0169] It can be seen from the results in Table 4 that the polymer coating formed by the vinylpyridine-butadiene block copolymer provided by the present invention has high peel strength with the copper foil, good interlayer bonding force between the copper foils, and low thermal expansion coefficient.

[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A vinylpyridine-butadiene block copolymer, characterized in that: Based on the total weight of the vinylpyridine-butadiene block copolymer, the content of the vinylpyridine segment is 2-10% by weight, and the content of the butadiene segment is 90-98% by weight; based on the total weight of the butadiene segment, the content of the 1,4-structural unit is 10-25% by weight, the content of the 1,2-structural unit is 50-70% by weight, and the content of the cyclized 1,2-structural unit is 15-35% by weight.

2. The vinylpyridine-butadiene block copolymer according to claim 1, wherein Based on the total weight of the vinylpyridine-butadiene block copolymer, the content of the butadiene segment is 92-96% by weight, and the content of the vinylpyridine segment is 4-8% by weight; Preferably, based on the total weight of the butadiene segment, the content of 1,4-structural units is 10-20 wt %; the content of 1,2-structural units is 50-65 wt %, preferably 52-62 wt %; the content of cyclized 1,2-structural units is 18-35 wt %, preferably 20-35 wt %; Preferably, the weight ratio of the cyclized 1,2-structural unit to the 1,2-structural unit in the vinylpyridine-butadiene block copolymer is 0.2-0.7:1, preferably 0.3-0.6:

1.

3. The vinylpyridine-butadiene block copolymer according to claim 1 or 2, wherein The number average molecular weight of the vinylpyridine-butadiene block copolymer is 3000-10000 g / mol, preferably 5000-8500 g / mol; Preferably, the molecular weight distribution index of the vinylpyridine-butadiene block copolymer is 1-1.25, preferably 1-1.15; Preferably, based on the total weight of the vinylpyridine-butadiene block copolymer, the weight content of the metal element in the polymer is 200 ppm or less, preferably 100 ppm or less.

4. The vinylpyridine-butadiene block copolymer according to any one of claims 1 to 3, wherein The linear thermal expansion coefficient of the vinyl pyridine-butadiene block copolymer after curing is 45×10 -6 m / m / ℃-80×10 -6 m / m / ℃, preferably 50×10 -6 m / m / ℃-75×10 -6 m / m / ℃, more preferably 50×10 -6 m / m / ℃-70×10 -6 m / m / ℃; Preferably, the peel strength between the coating formed by the vinylpyridine-butadiene block copolymer and the metal substrate is 0.9-1.1 N / mm, preferably 1.02-1.2 N / mm, and more preferably 1.05-1.2 N / mm; Preferably, after curing, the coating formed by the vinylpyridine-butadiene block copolymer has an interlayer bonding force on the metal substrate of 0.8-1.1 N / mm, preferably 0.86-1.1 N / mm, and more preferably 0.95-1.1 N / mm.

5. A method for preparing a vinylpyridine-butadiene block copolymer, characterized in that: The method comprises: (1) in the presence of a solvent, a structure regulator and an initiator, continuously adding 1,3-butadiene monomer into a reactor to carry out anionic solution polymerization reaction to obtain a polymerization reaction solution containing a butadiene polymer, wherein the contact is carried out at a temperature of 60-100° C., the structure regulator comprises component A and component B, the component A is a tertiary amine, the component B is an alkali metal alcohol salt, the molar ratio of the component B to the component A is 0.1-0.5:1, and the solvent is a solvent containing an aliphatic heterocyclic ring; (2) After the product obtained in step (1) is brought into contact with an alkyl metal compound for a first time, vinyl pyridine monomer is added for copolymerization to obtain a vinyl pyridine-butadiene block copolymer; wherein the amount of vinyl pyridine monomer added is 2-10 wt % based on the total weight of the 1,3-butadiene monomer and the vinyl pyridine monomer.

6. The method according to claim 5, wherein: The amount of the vinyl pyridine monomer added is 4-8 wt % based on the total weight of the 1,3-butadiene monomer and the vinyl pyridine monomer; Preferably, the copolymerization reaction conditions include: polymerization temperature of 20°C to 60°C, polymerization time of 10-30min; Preferably, the vinyl pyridine monomer is selected from 2-vinyl pyridine and / or 4-vinyl pyridine.

7. The method according to claim 5 or 6, wherein: Based on 100 g of solvent, the rate of adding 1,3-butadiene into the reactor is 0.1-0.5 g / min, preferably 0.15-0.35 g / min; Preferably, the 1,3-butadiene monomer is continuously produced at a temperature of 60°C to 90°C.

8. The method according to any one of claims 5 to 7, wherein: In step (2), the alkyl metal compound is selected from an alkyl aluminum compound and / or an alkyl magnesium compound; Preferably, the alkyl metal compound is at least one selected from trimethylaluminum, triethylaluminum, tripropylaluminum, triisopropylaluminum, tributylaluminum, triisobutylaluminum, diethylmagnesium, dibutylaluminum and n-butyl-sec-butylmagnesium; Preferably, the molar ratio of the alkyl metal compound to the initiator is 1-5:1, preferably 1-2:1; Preferably, the first contact time between the product obtained in step (1) and the alkyl metal compound is 1-10 min, preferably 2-8 min.

9. The method according to any one of claims 5 to 8, wherein: The component A is one or more compounds selected from the group consisting of: In formula I, R2 and R3 are the same or different and are independently C1-C6 alkyl groups, and R1 is a monovalent group shown in formula II, In formula II, m is an integer of 1-5, R4 and R5 are the same or different, and are independently a hydrogen atom or a C1-C6 alkyl group, R6 is -NR7R8 or a C3-C6 oxacycloalkyl group, R7 and R8 are the same or different, and are independently a C1-C6 alkyl group, Preferably, the component A is N,N,N',N'-tetramethylethylenediamine and / or N,N-dimethyl-tetrahydrofurfurylamine.

10. The method according to any one of claims 5 to 9, wherein: The component B is one or more compounds selected from the group consisting of: R9-O-M1 (Formula III) In formula III, R9 is C1-C 20 Alkyl, C1-C 20 Alkyl, or C6-C 30 The aromatic group, M1 is an alkali metal atom; Preferably, the heteroatom-containing substituent is a heteroatom-containing cycloalkyl group, and the heteroatom is preferably an oxygen atom, a sulfur atom or a nitrogen atom, more preferably an oxygen atom; Preferably, the component B is one or more of sodium tetrahydrofurfuryl alcohol, sodium tert-pentyl alcohol, sodium tert-butyl alcohol, sodium n-hexanolate and sodium menthol.

11. The method according to any one of claims 5 to 10, wherein: The molar ratio of the component B to the component A is 0.15-0.45:1, preferably 0.2-0.4:1; Preferably, the amount of component B used is 0.1-0.5 mol, preferably 0.2-0.4 mol, relative to 1 mol of the initiator.

12. The method according to any one of claims 5 to 11, wherein: The amount of the initiator is such that the number average molecular weight of the prepared vinylpyridine-butadiene block copolymer is 3000-10000 g / mol, preferably 5000-8500 g / mol; Preferably, the initiator is an organic lithium initiator, preferably one or more selected from the compounds shown in formula IV, R 10 Li (Formula IV) In Formula IV, R 10 C1-C6 alkyl, C3-C 12 Cycloalkyl, C7-C 14 Arylalkyl or C6-C 12 The aromatic group; More preferably, the anionic polymerization initiator is n-butyl lithium and / or sec-butyl lithium; Preferably, the solvent is an oxacycloalkane, preferably tetrahydrofuran.

13. A vinylpyridine-butadiene block copolymer prepared by the method according to any one of claims 5 to 12.

14. A composition comprising a vinyl pyridine-butadiene block copolymer and at least one additive, wherein the vinyl pyridine-butadiene block copolymer is the vinyl pyridine-butadiene block copolymer according to any one of claims 1 to 4 and 14.

15. The composition according to claim 14, wherein The additive contains an antioxidant.

16. A polymer coating comprising the vinylpyridine-butadiene block copolymer according to any one of claims 1 to 4 and 13, or the composition according to claim 14 or 15.

17. Use of the acrylate-butadiene block polymer according to any one of claims 1 to 4 and 14, or the composition according to any one of claims 15 or 16 as a crosslinking agent, an adhesive or an electrical insulating material.

Citation Information

Patent Citations

  • Liquid polybutadiene, preparation method and application thereof, composition, polymer coating, adhesive and cross-linking agent

    CN113698520A

  • Preparation method of liquid butadiene polymer, liquid butadiene polymer, liquid butadiene polymer product and application

    CN114106228A